Redux redux [videorecording (DVD)] - McManus, Michaela, 1983-; Marcus, Stella; Holm, Jeremy; Cummings, Jim (Film director) (Sony Pictures Home Entertainment, 2026)
In an attempt to avenge her daughter's death, Irene Kelly travels through parallel universes, killing her daughter's murderer over and over again. She grows addicted to the revenge streak, putting her own humanity in jeopardy.